The process of communicating issues about the meaninglessness of human life appeared in Eugene O’Neill’s Thirst through theatre directing - Pruerklerttrakul, Attakrit; Na Pombejra, Dangkamon (Journal of Music and Performing Arts Khon Kaen University, 2025)
This research from the researcher’s interpretation that the realism theatre style play in Eugene O’Neill’s THIRSThas the main idea and important issue about the meaninglessness of human life, which is one of the ideas from the theatre of the absurd. The researcher, as the theatre director, had a question: How can the directing process be used to communicate the idea from the theatre of the absurd in a realism theatre style? Therefore, the objective is to study and experiment with the appropriate directing process for communicating to answer that question. The researcher used creative research methods. Analyze and collect relevant information to create a conceptual framework to understand the details of such issues hidden in the content of the play. It is then analysed and interpreted according to principles for theatre directing to find a message (main idea), objective, action, and conflict. Then compile and prepare information for directing. during practice, the researcher used a substitution method in each sequence situation of the play with the acter’s experiences and imagination. Mainly using the method of Stella Adler’s acting techniques to help review and create an understanding of the characterization for the actors and to experiment with learning and development throughout the rehearsal period until the performance to the public. The research results showed that when the researcher has a conceptual framework for the issue of the meaninglessness of human life. It helps connect for analysis and interpretation of the play. Makes the researcher’s thought process clearly understand the details of the play (especially the play’s message) and builds confidence when directing. The content in the play can be communicated to the actors as well as the audience so that they can feel involved in the realism theatre style. In addition, this research process may be a guideline and method to help the director practice finding the message of the play to be precisely understood and be aware of what you want to communicate, including, priorities from using the message to guide the exploration of presentation for theatre’s style with a clearer direction.